2017
DOI: 10.3390/nu9090939
|View full text |Cite
|
Sign up to set email alerts
|

Salt Use Behaviours of Ghanaians and South Africans: A Comparative Study of Knowledge, Attitudes and Practices

Abstract: Salt consumption is high in Africa and the continent also shares the greatest burden of hypertension. This study examines salt-related knowledge, attitude and self-reported behaviours (KAB) amongst adults from two African countries—Ghana and South Africa—which have distributed different public health messages related to salt. KAB was assessed in the multinational longitudinal World Health Organisation (WHO) study on global AGEing and adult health (WHO-SAGE) Wave 2 (2014–2015). Respondents were randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…Poor salt use behavior is widespread in the Ghanaian population; a previous study involving 12 villages in Ghana in 2006 reported that 98% of participants added salt to food during cooking, while about half (52%) added salt to food at the table [21]. In comparison to South Africans, Ghanaians reported adding salt to food during cooking more frequently [45], presumably because mass media public health campaigns to lower salt use, such as Salt Watch in South Africa have not yet occurred in Ghana [46]. Further, Ghana's national salt iodization programme, along with accompanying major public health campaigns on iodine consumption [47][48][49][50] may partially be responsible for an increase in discretionary salt intake.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Poor salt use behavior is widespread in the Ghanaian population; a previous study involving 12 villages in Ghana in 2006 reported that 98% of participants added salt to food during cooking, while about half (52%) added salt to food at the table [21]. In comparison to South Africans, Ghanaians reported adding salt to food during cooking more frequently [45], presumably because mass media public health campaigns to lower salt use, such as Salt Watch in South Africa have not yet occurred in Ghana [46]. Further, Ghana's national salt iodization programme, along with accompanying major public health campaigns on iodine consumption [47][48][49][50] may partially be responsible for an increase in discretionary salt intake.…”
Section: Discussionmentioning
confidence: 96%
“…sugar, syrup, ice cream, candy, and carbonated and noncarbonated sweetened drinks). Additionally, frequent consumption of highly salted foods, such as fish and meat, remains part of the traditional Ghanaian cuisine, and salt use in cooking remains high [42,45].…”
Section: Discussionmentioning
confidence: 99%
“…Such differences would need to be considered in policy development. It is clear that salt reduction strategies in Ghana would need to focus both on salt reduction in the food supply, as well as efforts to raise consumer awareness on discretionary salt use in cooking and added to foods at the table in Ghana ( 27 ).…”
Section: New Data On Salt Intake In Ghanamentioning
confidence: 99%
“…In Ghana, the majority of the population consume processed foods that are high in salt ( 14 ) and report a high use of discretionary salt added to foods at the table and in food preparation ( 27 ). Rapid urbanization, population growth, and changing lifestyles have resulted in a rapid nutrition transition in the country and that has resulted in an increased intake of processed foods ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, this knowledge did not seem to translate into attitudes and practices related to salt intake reduction. For example, participants were frequently unable to correctly identify the maximum recommended daily salt intake, nor were they aware of the link between salt and sodium, and generally did not perceive their salt intake to be high 25,27,32,41,55,56,59 . The latter may contribute to the low proportion of participants who reported adopting practices known to reduce salt consumption observed in the included studies.…”
Section: Discussionmentioning
confidence: 97%